Neuroimmune regulation of female reproduction in health and disease. (August 2019) - Fuller, Erin A; Younesi, Simin; Xavier, Soniya; Sominsky, Luba
Highlights: Microglia and astrocytes regulate the development and function of central reproductive circuitry. Chronic inflammation disrupts ovarian and uterine function and may lead to infertility. Immune and neuroimmune adaptations are essential for pregnancy success. Abstract : Female reproductive development and function are tightly regulated by immune and endocrine interactions centrally, peripherally and locally within the utero-ovarian environment. This hormonal-immune cross talk is implicated in the major milestones of female reproduction, including ovarian development, ovulation, menstruation, implantation and pregnancy. Excessive immune activation and hyperinflammatory states appear to be associated with several immune-based reproductive disorders and infertility. However, in recent years it has become increasingly apparent that an appropriately functioning immune system is essential for all aspects of reproductive function. Here, we will review recent discoveries examining the impact of immune regulators on female reproductive development and fertility. We will specifically highlight the role of glial cells and the ovarian and uterine immune interface in gonadal and pubertal development, in the regulation of adult reproductive behaviour, as well as in fertility and pregnancy.